Preexisting autoantibodies as predictor of immune related adverse events (irAEs) for advanced solid tumors treated with immune checkpoint inhibitors (ICIs) - A Daban; C Gonnin; L Phan; A Saldmann; C Granier; A Lillo-Lelouet; C Le Beller; J Pouchot; l Weiss; E Tartour; E Fabre; J Medioni; et al. (OncoImmunology)
Introduction: Immune checkpoint inhibitors (ICIs) are now standard of care in many cancers. They can generate immune-related adverse events (irAEs), but no biomarkers are available to identify patients who are more likely to develop irAEs. We assess the association between pre-existing autoantibodies and occurrence of irAEs. Patients and Methods: We prospectively collected data from consecutive patients receiving ICIs for advanced cancers, in a single center between May 2015 and July 2021. Autoantibodies testing was performed before ICIs initiation including AntiNeutrophil Cytoplasmic Antibodies, Antinuclear Antibodies, Rheumatoid Factor anti-Thyroid Peroxidase and anti-Thyroglobulin. We analyzed the associations of pre-existing autoantibodies with onset, severity, time to irAEs and with survival outcomes. Results: Of the 221 patients included, most had renal cell carcinoma (n = 99; 45%) or lung carcinoma (n = 90; 41%). Grade ≥2 irAEs were more frequent among patients with pre-existing autoantibodies: 64 (50%) vs. 20 (22%) patients (Odds-Ratio= 3.5 [95% CI=1.8-6.8]; p < 0.001) in the positive vs negative group, respectively. irAEs occurred earlier in the positive group with a median time interval between ICI initiation and irAE of 13 weeks (IQR = 8.8-21.6) vs. 28.5 weeks (IQR=10.6-55.1) in the negative group (p = 0.01). Twelve patients (9.4%) experienced multiple (≥2) irAEs in the positive group vs. 2 (2%) in the negative group (OR = 4.5 [95% CI: 0.98-36], p = 0.04). After a median follow-up of 25 months, median PFS and OS were significantly longer among patients experiencing irAE (p = 0.00034 and p = 0.016, respectively). Conclusion: The presence of pre-existing autoantibodies is significantly associated with the occurrence of grade ≥2 irAEs, with earlier and multiple irAEs in patients treated with ICIs.